Should I stay or should I go? The role of individual strivings in shaping the relationship between envy and avoidance behaviors at work. (7th January 2022) - Tussing, Danielle V.; Wihler, Andreas; Astandu, Timothy V.; Menges, Jochen I.
Summary: Research on envy is dominated by a focus on approach‐oriented behaviors—when envious employees take action to reduce the gap between the self and envied targets. Surprisingly, little research has examined the relationship between envy and avoidance‐oriented behaviors, even though emotion regulation research suggests that avoidance is a common reaction to unpleasant, painful emotions such as envy. We seek to understand envy's consequences for workplace avoidance—namely, absenteeism and turnover. Drawing on theories about how people interpret and regulate emotions according to their goals, we suggest that employees' individual differences in motivational strivings shape the relationship between envy and avoidance behaviors. We propose that for employees high in communion or status striving, envy is associated with more absences and thereby increased turnover; for employees high in achievement striving, envy is associated with fewer absences and ultimately reduced turnover. A field study of supermarket employees shows general support for our conceptual model regarding communion and achievement strivings but a null effect for status striving. Our research expands the nomological network of envy by examining its impact on workplace avoidance, helps to shed light on contradictory findings in envy research, and offers implications for theories on work motivation, emotions, and avoidance behaviors.